Answer: x=10 Step-by-step explanation: Let x = the number Solve: x + (-6) = 4 Subtract -6 on both sides ( or as add 6 on both sides) x + (-6) – (-6) = 4 – (-6) x=10 Log in to Reply

Answer: x=10 Step-by-step explanation: Let x = the number Solve: p + (-6) = 4 p + (-6) – (-6) = 4 – (-6) Log in to Reply

Answer: x=10Step-by-step explanation:Let x = the number

Solve:x + (-6) = 4

Subtract -6 on both sides ( or as add 6 on both sides)x + (-6) – (-6) = 4 – (-6)

## x=10

Answer: x=10

Step-by-step explanation:

Let x = the number

Solve:

p + (-6) = 4

p + (-6) – (-6) = 4 – (-6)